2019
DOI: 10.1021/acs.chemmater.9b03529
|View full text |Cite
|
Sign up to set email alerts
|

Alkyl Phosphonic Acids Deliver CsPbBr3 Nanocrystals with High Photoluminescence Quantum Yield and Truncated Octahedron Shape

Abstract: We devised a colloidal approach for the synthesis of CsPbBr 3 nanocrystals (NCs) in which the only ligands employed are alkyl phosphonic acids. Compared to more traditional syntheses of CsPbBr 3 NCs, the present scheme delivers NCs with the following distinctive features: (i) The NCs do not have cubic but truncated octahedron shape enclosed by Pb-terminated facets. This is a consequence of the strong binding affinity of the phosphonate groups toward Pb 2+ ions. (ii) The NCs have near unity photoluminescence qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
232
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(246 citation statements)
references
References 40 publications
12
232
1
1
Order By: Relevance
“…Various studies have demonstrated that a simple variation of the local pH, which can cause protonation/deprotonation of carboxylate/oleylammonium ions, or even a dilution of the NC suspension, which decreases the chemical potential of the free ligands with respect to that of bound ones, can lead to ligands detachment, which is deleterious for both colloidal stability and PL. 9 , 12 Consequently, these types of ligands are weakly bound to the NCs surface, and a highly dynamic equilibrium exists between free and bound ligands. 9 , 13 15 In order to optimize the surface passivation of LHP NCs, various alternative surfactants have been investigated, with zwitterionic molecules, quaternary alkyl ammonium ions, and sulfonic and alkyl phosphonic acids being the most promising ones.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have demonstrated that a simple variation of the local pH, which can cause protonation/deprotonation of carboxylate/oleylammonium ions, or even a dilution of the NC suspension, which decreases the chemical potential of the free ligands with respect to that of bound ones, can lead to ligands detachment, which is deleterious for both colloidal stability and PL. 9 , 12 Consequently, these types of ligands are weakly bound to the NCs surface, and a highly dynamic equilibrium exists between free and bound ligands. 9 , 13 15 In order to optimize the surface passivation of LHP NCs, various alternative surfactants have been investigated, with zwitterionic molecules, quaternary alkyl ammonium ions, and sulfonic and alkyl phosphonic acids being the most promising ones.…”
mentioning
confidence: 99%
“… 9 , 13 15 In order to optimize the surface passivation of LHP NCs, various alternative surfactants have been investigated, with zwitterionic molecules, quaternary alkyl ammonium ions, and sulfonic and alkyl phosphonic acids being the most promising ones. 3 , 9 , 12 , 16 , 17 The improved stability in these cases arises from the fact that either they cannot be deprotonated (zwitterionic molecules, quaternary alkylammonium ions), or they have a strong affinity toward surface Pb 2+ ions (sulfonic and phosphonic acids). As a result, all these ligands yield LHP NCs with higher stability and near-unity PL quantum yield (QY).…”
mentioning
confidence: 99%
“…Further interesting binding chemistry with phosphonic acids was reported by Zhang et al [76] They discovered that the conditions of the hot-injection method drove a condensation reaction, forming phosphonic acid anhydrides from phosphonic acids. These phosphonic acid anhydride species could then form bidentate bonds to the CsPbBr 3 NC surface (Figure 11a), presumably because the distance between adjacent hydroxyl groups on the anhydride was similar to the spacing between lead sites of the NC.…”
Section: Phosphonic Acidsmentioning
confidence: 94%
“…Typically, short esters have been most successful. Depending on the ligand system employed, butyl acetate, [44] ethyl acetate, [35,41,43,[71][72][73][74][75][76][77] mixtures of ethyl and methyl acetate, [78,79] and methyl acetate alone, [67,[80][81][82][83] have been employed. Figure 6 shows a screening study of 36 potential antisolvents, it concurred on the efficacy of short esters, but indicated that diethylene glycol dimethyl ether (diglyme) was the most effective.…”
Section: Antisolvent Purificationmentioning
confidence: 99%
See 1 more Smart Citation